Historical Directory of Trade Unions : Volume 4, Including Unions in Cotton, Wood and Worsted, Linen and Jute, Silk, Elastic Web, Lace and Net, Hosiery and Knitwear, Textile Finishing, Tailors and Garment Workers, Hat and Cap, Carpets and Textile Engineering /: Volume 4, Including Unions in Cotton, Wood and Worsted, Linen and Jute, Silk, Elastic Web, Lace and Net, Hosiery and Knitwear, Textile Finishing, Tailors and Garment Workers, Hat and Cap, Carpets and Textile Engineering. (2016) - Marsh, Arthur, 1922-1999; Ryan, Victoria
No abstract available